2012
DOI: 10.1182/blood-2011-08-376046
|View full text |Cite
|
Sign up to set email alerts
|

IgG1 and IVIg induce inhibitory ITAM signaling through FcγRIII controlling inflammatory responses

Abstract: Intravenous immunoglobulin (IVIg) has been used in the treatment of several autoimmune and inflammatory diseases. However, its mechanism of action remains incompletely understood. Here, we investigated the possibility that IVIg induces its anti-inflammatory effects through activating Fc␥ receptors bearing an immunoreceptor tyrosine-based activation motif (ITAM) in the FcR␥ signaling adaptor. Recently, the concept of inhibitory ITAM (ITAMi) has emerged as a new means to negatively control the immune response. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
79
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 49 publications
(86 reference statements)
5
79
0
1
Order By: Relevance
“…on May 11, 2018. by guest www.bloodjournal.org From reflects antigen uptake/endocytic ability, 36 a defining property of immature DCs. However, an increased ability to capture antigens via receptor-mediated endocytosis has also been demonstrated in mature DCs 37 and has been proposed to confer mature DCs with the ability to capture and present specific antigens and pathogens previously recognized by the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…on May 11, 2018. by guest www.bloodjournal.org From reflects antigen uptake/endocytic ability, 36 a defining property of immature DCs. However, an increased ability to capture antigens via receptor-mediated endocytosis has also been demonstrated in mature DCs 37 and has been proposed to confer mature DCs with the ability to capture and present specific antigens and pathogens previously recognized by the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…The FcR␥-chain is, indeed, also required for the expression of macrophage-inducible C-type lectin (Mincle) 44 and osteoclast-associated receptor (OSCAR), 45 and contributes to the signal transduction of several other molecules. Fc␥RIIB Ϫ/Ϫ mice were reported in 1996, 46 Fc␥RIII Ϫ/Ϫ mice in 1996 47 and 1999, 48 [61][62][63][64] have also been reported to be involved/mandatory. Indeed, an increasing number of reports have revealed that activating Fc␥RIII mediates the anti-inflammatory effects of intravenous immunoglobulin in experimental thrombocytopenia when expressed on DCs 61 or on macrophages, 62 in allergic airway inflammation when expressed on NKT cells, 63 and in a nonimmune inflammation model of obstructive nephropathy.…”
Section: Data Using Fc␥r-deficient Micementioning
confidence: 99%
“…Indeed, an increasing number of reports have revealed that activating Fc␥RIII mediates the anti-inflammatory effects of intravenous immunoglobulin in experimental thrombocytopenia when expressed on DCs 61 or on macrophages, 62 in allergic airway inflammation when expressed on NKT cells, 63 and in a nonimmune inflammation model of obstructive nephropathy. 64 Using knockout mice for a particular FcR was for a long time considered the standard approach to address the function of a particular Fc␥R in vivo (ie, by studying the effect of its absence). Recently, however, the generation of multiple FcR-knockout mice has enabled the study of a particular FcR in the absence of most/all other FcRs.…”
Section: Data Using Fc␥r-deficient Micementioning
confidence: 99%
“…However, it is unknown how the inhibitory FcgRIIB is involved in our ADCP system as compared with FcgRIA and FcgRIIA. In addition, FcgRIII was reported not only to exert phagocytosis but also to induce inhibitory signalling (28). In our previous study, interchain S S bond cleavage of rituximab resulted in increased binding affinity for FcgRIIIA and decreased ADCC (19), suggesting inhibitory signalling through FcgRIIIA.…”
Section: Discussionmentioning
confidence: 99%